2017
DOI: 10.1037/fsh0000281
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Resilience in Stress Management for Parents (PRISM-P): An intervention for caregivers of youth with serious illness.

Abstract: Introduction It is well-known that parental stress and coping impacts the well-being of children with serious illness. The current study aimed to evaluate the feasibility and satisfaction of a novel resilience promoting intervention, the Promoting Resilience in Stress Management Intervention for Parents (PRISM-P) among parents of adolescents and young adults with type 1 diabetes or cancer. Secondary analyses explored the effect of the PRISM-P on parent-reported resilience and distress. Methods The PRISM-P in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 52 publications
4
53
0
3
Order By: Relevance
“…The completion rate of PRISM in the enrolled AYA CF population was high with 90% of the pilot sample completing all four interventions either as inpatient or in the outpatient setting in the proposed time frame. The completion rate in this study was comparable to previous resilience studies in the chronic patient populations, suggesting that once they actually start the intervention they are very likely to finish it . Even though participants agreed that the intervention was more productive and engaging in person, the phone option provided flexibility and convenience and increased the completion rate for all sessions.…”
Section: Discussionsupporting
confidence: 66%
“…The completion rate of PRISM in the enrolled AYA CF population was high with 90% of the pilot sample completing all four interventions either as inpatient or in the outpatient setting in the proposed time frame. The completion rate in this study was comparable to previous resilience studies in the chronic patient populations, suggesting that once they actually start the intervention they are very likely to finish it . Even though participants agreed that the intervention was more productive and engaging in person, the phone option provided flexibility and convenience and increased the completion rate for all sessions.…”
Section: Discussionsupporting
confidence: 66%
“…Five out of the 41 studies measured resiliency as an outcome of an intervention programme. Three interventions aimed at directly improving resiliency in youth with CHD (Lee et al, ), parents of children with ASD (Pandya et al, ), and parents of children with cancer or diabetes (Yi‐Fraizer et al, ). Lee et al () developed a resiliency improvement programme for adolescents with CHD, targeting five key psychosocial protective factors (i.e., positive emotions, cognitive flexibility, meaning, social support, and coping style).…”
Section: Resultsmentioning
confidence: 99%
“…RS was employed to measure parent resiliency, and the author reported that parent resiliency was increased post‐programme. Yi‐Fraizer et al () found that a resiliency promotion intervention targeting parents of children with type 1 diabetes improved the parents' ability to cope with stress. The intervention comprised four skill‐based modules and resiliency was measured by CD‐RISC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But caregiving is also a multidimensional experience associated with benefits, such as personal growth and positive meaning-making. 3 As pediatric healthcare providers, an integral and critical component of our comprehensive management of young people must encompass the primary caregivers and the family. Research shows the connection between caregiver wellbeing (physical and mental) and child functioning.…”
mentioning
confidence: 99%